Evaluation of a contra-rotating flux-modulated machine featured with dual flux-modulation for wind power generation - Chen, Hao (2022)
This paper presents an investigation of an integrated flux-modulated machine for wind power generation. This machine has two rotors which function as two contra-rotating rotors connected to two sets of turbine blades. Hence, compared to conventional wind generators, more wind energy could be captured by this system. Moreover, the integrated machine consists of two sets of stator windings. By regulating the currents in these windings, dual maximum power point tracking control strategy could be achieved. As a result, the wind power conversion efficiency is further improved. Moreover, this wind power generation system exhibits the advantage of high torque/power density due to the enhanced magnetic-gearing effect involved in the integrated flux-modulated machine. Hence, this machine is more suitable for direct-drive wind power generation, where the reliability is improved without the issues related to mechanical gearboxes. The topology and operating principle of the investigated machine are demonstrated. Decoupled design of the two sets of windings is investigated, and a general rule to achieve decoupled windings is illustrated. The advantages of the investigated machine are confirmed in comparison to a benchmark machine. Finally, the investigated machine is prototyped. The validity of the operating principle and the simulation results are verified by experimental results.